2024
DOI: 10.1029/2023gl107645
|View full text |Cite
|
Sign up to set email alerts
|

On the Scale of Particle Clustering Induced by Inhomogeneous Entrainment‐Mixing in Mixed‐Phase Cumulus Clouds

Yiting Liu,
Jing Yang,
Guozheng Zhao
et al.

Abstract: In mixed‐phase cumulus clouds, droplets and ice crystals are inhomogeneously distributed, such spatial inhomogeneity can be enhanced by inhomogeneous entrainment as it can strengthen the particle clustering, which may further influence the phase partitioning and interactions among hydrometeors. However, the scale of particle clustering induced by inhomogeneous entrainment is not well known. Utilizing high‐resolution in‐situ aircraft measurements in mixed‐phase cumulus clouds, this study shows due to inhomogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Li et al 34 illustrated that the drag of downstream particles was changed caused by the change of uniformity of flow behaviors inside the cluster. Liu et al 35 indicated that the heterogeneous entraining and mixing behaviors of droplets and ice crystals destroyed the spatial stability of clusters, causing the change of cluster scales.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 34 illustrated that the drag of downstream particles was changed caused by the change of uniformity of flow behaviors inside the cluster. Liu et al 35 indicated that the heterogeneous entraining and mixing behaviors of droplets and ice crystals destroyed the spatial stability of clusters, causing the change of cluster scales.…”
Section: Introductionmentioning
confidence: 99%